Raw data for shrimp feeding study based on insects reared on plant by-products - Barth, Annalena; Wilke, Thomas; Justus Liebig University Giessen (My University, 2024)
The dataset contains the raw data of randomized controlled feeding trial, which aimed at testing whether black soldier flies (BSF) reared on widely available but underutilized plant by-products such as cocoa bean shells, depectinized apple pomace and potato peelings may serve as sustainable feeds for Pacific white shrimp (PWS) aquaculture. The dataset consists of four sheets: 1. Raw data for the nutritional profiles of (cocoa bean shells, depectinized apple pomace, potato peelings and a grain-based control feed (FM = fresh matter, DM = dry matter), 2. Raw data for the nutritional profiles of black soldier fly (BSF) larvae reared on cocoa bean shells, depectinized apple pomace, potato peelings and a grain-based control feed (FM = fresh matter, DM = dry matter), 3. Raw data for growth curves, larval development time and final weight of black soldier fly (BSF) larvae reared on three plant by-products (CBS: cocoa bean shells, DAP: depectinized apple pomace, PP: potato peelings) and a grain-based control feed, 4. Raw data for feeding regimes, growth characteristics and feed conversion parameters of Pacific white shrimp (PWS) fed with black soldier fly (BSF) based diets where BSF larvae were reared on cocoa bean shells, depectinized apple pomace, potato peelings and a grain -based control feed.
Keywords: Aquaculture; ddc:333.7; ddc:590